2021
DOI: 10.1097/icl.0000000000000860
|View full text |Cite
|
Sign up to set email alerts
|

Noninferiority Study Comparing Latanoprost 0.005% Without Versus With Benzalkonium Chloride in Open-Angle Glaucoma or Ocular Hypertension

Abstract: Objectives: To evaluate the noninferiority of intraocular pressure (IOP)lowering latanoprost without benzalkonium chloride (BAK) versus latanoprost with BAK (for treatment of open-angle glaucoma or ocular hypertension). Methods: Overall, 578 patients were randomized 1:1 to latanoprost without BAK or latanoprost with BAK once daily in the affected eye(s) for 12 weeks. The primary efficacy endpoint was IOP, measured on days 0, 7, 28, 56, and 84 (8 AM, 10 AM, and 4 PM). Noninferiority was established if the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The current findings are consistent with other recent publications that collectively support the safety, tolerability, and high rates of patient satisfaction and self-reported quality of life with BAK-free latanoprost formulations, including preservativefree formulations. [8][9][10][11][12][13][14][15] Results of the 12-week primary phase 3 study comparing latanoprost 0.005% without vs with BAK in OAG or OHT, which enrolled 578 patients, demonstrated that substantial reductions from baseline in IOP were maintained for the duration of the study in the latanoprost BAK-free group. 8 TEAEs were mostly mild with comparable incidence between treatment groups, and no significant safety concerns were found for ocular TEAEs (eye pain, ocular and conjunctival hyperemia, VA, eye lid and margin, cornea, anterior chamber, eye pruritus, VF, and iris and eyelash changes) in patients receiving BAK-free latanoprost.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current findings are consistent with other recent publications that collectively support the safety, tolerability, and high rates of patient satisfaction and self-reported quality of life with BAK-free latanoprost formulations, including preservativefree formulations. [8][9][10][11][12][13][14][15] Results of the 12-week primary phase 3 study comparing latanoprost 0.005% without vs with BAK in OAG or OHT, which enrolled 578 patients, demonstrated that substantial reductions from baseline in IOP were maintained for the duration of the study in the latanoprost BAK-free group. 8 TEAEs were mostly mild with comparable incidence between treatment groups, and no significant safety concerns were found for ocular TEAEs (eye pain, ocular and conjunctival hyperemia, VA, eye lid and margin, cornea, anterior chamber, eye pruritus, VF, and iris and eyelash changes) in patients receiving BAK-free latanoprost.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] Results of the 12-week primary phase 3 study comparing latanoprost 0.005% without vs with BAK in OAG or OHT, which enrolled 578 patients, demonstrated that substantial reductions from baseline in IOP were maintained for the duration of the study in the latanoprost BAK-free group. 8 TEAEs were mostly mild with comparable incidence between treatment groups, and no significant safety concerns were found for ocular TEAEs (eye pain, ocular and conjunctival hyperemia, VA, eye lid and margin, cornea, anterior chamber, eye pruritus, VF, and iris and eyelash changes) in patients receiving BAK-free latanoprost. 8 A post hoc pooled analysis of 3 randomized controlled clinical trials and 2 international real-world evidence observational studies including 3610 total patients, which compared patient tolerance and efficacy of preservative-free and preservative-containing latanoprost formulations, found that patients receiving preservative-free latanoprost had reductions in conjunctival hyperemia and ocular surface disease composite score as compared with patients receiving latanoprost with preservatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that the bioequivalence of the formulations was not achieved. They reported a greater reduction in IOP in the group of patients using BAK-containing formulations [8].…”
Section: Efficacy Of Medicines Containing Preservativesmentioning
confidence: 95%
“…If preservative-free formulations (the study group) are not as efficient as preservative-containing formulations, then, since the active ingredient is the same, drug efficacy depends on the presence of the preservative. Wirta et al, in a study published in 2022, did not confirm the bioequivalence of a BAK-free latanoprost with latanoprost containing BAK at 0.05% concentration [8]. In the study, patients were randomly assigned in a ratio of 1 : 1 to either a group without BAK or to a reference group with BAK.…”
Section: Efficacy Of Medicines Containing Preservativesmentioning
confidence: 99%